Investigation of the Effect of Gamified Learning on Motivation and Success in Math Class - KarabÄ±yÄ±k, Ãœmit (Journal of Education and Practice, 2024)
Purpose: Educators are consistently seeking ways to enhance classroom engagement. In response to declining student achievement in mathematics, traditional teaching methods are gradually giving way to more innovative approaches such as gamified learning. Gamified learning complements conventional instruction by creating an engaging virtual and augmented reality environment in which students can actively interact with the subject matter. This study revolves around a highly significant research question: the impact of gamified learning in mathematics education on student motivation and achievement. In this domain, investigations into the latest developments in designing and testing mathematical games have been examined. Methodology: To this end, a literature review method has been employed, and document analysis has been conducted. Findings: The results indicate that gamified learning proves to be a promising tool for enhancing short-term motivation and student achievement. Unique contributor to theory, policy and practice: However, further research is necessary to determine if these gains can be sustained over the course of a semester.